The Underling Mechanisms Exploration of Rubia cordifolia L. Extract Against Rheumatoid Arthritis by Integrating Network Pharmacology and Metabolomics - Zeng W; Fang Y; Mo S; Shen C; Yang H; Luo G; Xiao L; Zhan R; Yan P (Drug Design, Development and Therapy, 2023)
Weiya Zeng,1– 3 Yuan Fang,1– 3 Suifen Mo,1– 3 Caihong Shen,1– 3 Huiling Yang,1– 3 Guihua Luo,1– 3 Luhua Xiao,1– 3 Ruoting Zhan,1– 3 Ping Yan1– 3 1College of Traditional Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2Key Laboratory of Chinese Medicinal Resources from Lingnan (Guangzhou University of Chinese Medicine), Ministry of Education, Guangzhou, People’s Republic of China; 3Joint Laboratory of Nation Engineering Research Center for the Pharmaceutics of Traditional Chinese Medicines, Guangzhou, People’s Republic of ChinaCorrespondence: Ruoting Zhan; Ping Yan, Guangzhou University of Chinese Medicine, No. 232, Outer Ring East Road, Guangzhou, Guangdong, People’s Republic of China, Tel/Fax +86 20-39358045, Email ruotingzhan@vip.163.com; yanping@gzucm.edu.cnPurpose: Rubia cordifolia L. (RC) is a classic herbal medicine for the treatment of rheumatoid arthritis (RA) and has been used since ancient times. The ethanol extract of Rubia cordifolia L. (RCE) showed obvious anti-RA effects in our previous study. However, further potential mechanisms require more exploration. We aimed to investigate the mechanism of RCE for the treatment of RA by integrating metabolomics and network pharmacology in this study.Methods: An adjuvant-induced arthritis (AIA) rat model was established, and we evaluated the therapeutic effects of RCE. Metabolomics of serum and urine was used to identify the differential metabolites. Network pharmacology was applied to determine the key metabolites and potential targets. Finally, the potential targets and compounds of RCE were verified by molecular docking.Results: The results indicated that RCE suppressed foot swelling and alleviated joint damage and also had anti-inflammatory properties by inhibiting the expressions of tumor necrosis factor (TNF)-α, Interleukin (IL)-1β, prostaglandin E2 (PGE2), and P65. Ten and seven differential metabolites were found in the serum and urine, respectively, of rats. Six key targets, ie, phospholipase A2 group IIA (PLA2G2A), phospholipase A2 group X (PLA2G10), cytidine deaminase (CDA), uridine-cytidine kinase 2 (UCK2), charcot-leyden crystal galectin (CLC), and 5′,3′-nucleotidase, mitochondrial (NT5M), were discovered by network pharmacology and metabolite analysis and were found to be related to glycerophospholipid metabolism and pyrimidine metabolism. Molecular docking confirmed that the favorable compounds showed affinities with the key targets, including alizarin, 6-hydroxyrubiadin, ruberythric acid, and munjistin.Conclusion: This study revealed the underlying mechanisms of RCE and provided evidence that will allow researchers to further investigate the functions and components of RCE against RA.Keywords: inflammtion, AIA rats, molecular docking, chronic disease